Будь ласка 33 завдання

Будь ласка 33 завдання
Гость
Ответ(ы) на вопрос:
Гость
[latex]( \frac{5m}{m+3} - \frac{14m}{(m+3)^2} ) : \frac{5m+1}{m^2-9} + \frac{3(m-3)}{m+3} = \\ \\ = \frac{5m(m+3)-14m}{(m+3)^2} * \frac{m^2-9}{5m+1} +\frac{3(m-3)}{m+3} = \\ \\ = \frac{5m^2+15m-14m}{(m+3)^2} * \frac{(m-3)(m+3)}{5m+1} +\frac{3(m-3)}{m+3} = \\ \\ =\frac{m(5m+1)}{(m+3)^2} * \frac{(m-3)(m+3)}{5m+1} +\frac{3(m-3)}{m+3} = \\ \\ = \frac{m(m-3)}{m+3} +\frac{3(m-3)}{m+3} = \frac{m(m-3)+3(m-3)}{m+3} = \\ \\ = \frac{(m-3)(m+3)}{m+3} = \frac{m-3}{1} = m-3[/latex] Ответ: 1) m-3
Не нашли ответ?
Ответить на вопрос
Похожие вопросы